Collagen Cross-Linking Therapy on Important Functional Genes Involved in Keratoconus Patients Using Protein-Protein Interactions (PPI) Network and Differential Expression Analysis - Maghsoudloo, Mazaher; Hafez Noroozizadeh, Mohammad (Journal of Ophthalmic and Optometric Sciences, 2019)
Keratoconus (KC) is a progressive eye condition marked by corneal protrusion, thinning, and scarring that adversely affects the ability to see and quality of life. A defective corneal extracellular matrix (ECM) assembly ultimately results in myopia, irregular astigmatism, and severe visual impairment. Most commonly occurring in adolescence, this condition is one of the most commonly indicated clinical indications for corneal transplantation. In contrast to corneal transplantation, corneal collagen crosslinking (CXL) increases corneal stiffness without inflicting any invasive surgery. This study used RNA-Seq data to investigate which functional genes are regulated by CXL in keratoconus. The RNA-Seq expression matrix related to individuals with Keratoconus (KC) and patients treated with collagen crosslinking (CXL) were obtained from the Gene Expression Omnibus (GEO)[1] database 1at the National Center for Biotechnology Information (NCBI) were retrieved. Differential expression analysis and functional enrichment analysis were conducted. The hub genes were then identified with the protein-protein interactions (PPI) network. Finally, transcription factor (TF) genes were identified that regulate these networks. We identified 126 genes in KC and CXL-treated patients that affect TF-mediated network adjustments that improve treatment. In addition, they may play a role in the pathogenesis of keratoconus. Visualization of the PPI networks enabled us to identify 63 highly connected (Hub) genes which served an essential biological function in regulatory networks.